PENGARUH BRAND IMAGE, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO RISKI PAKAN BURUNG DI SITUBONDO DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING - Bulu, Darius; Pramitasari, Triska Dewi; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Marketing is an interconnected activity between companies and consumers as a system for generating profits, therefore having the right marketing strategy can improve it, especially as a means of developing the Riski Bird Feed Shop. The aim of this research is to analyze and test the influence of Brand Image, Price and Promotion on Purchasing Decisions through Trust as an intervening variable. The target population in this research was the consumers of the Riski Bird Feed Shop, numbering 97 respondents. This sampling technique is simple random sampling. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that brand image has a significant positive effect on trust. Price has a significant positive effect on Trust. Promotion has a significant positive effect on Trust. Brand image has a positive but not significant effect on purchasing decisions. Price has a positive but not significant effect on purchasing decisions. Promotion has a significant positive effect on purchasing decisions. Trust has a significant positive effect on purchasing decisions. Then the results of the indirect influence hypothesis test show that the Brand image variable on purchasing decisions through Trust has a significant positive effect. Price on purchasing decisions through Trust has a significant positive effect. Promotion of purchasing decisions through Trust has a significant positive effect